Exploring the Prevalence of Oral Features for Early Detection of PTEN Hamartoma Tumour Syndrome - Ane J. Schei-Andersen; Bart van Oirschot; Meggie M.C.M. Drissen; Jolanda Schieving; Janneke H.M. Schuurs-Hoeijmakers; Janet R. Vos; Claire M. Barton; Nicoline Hoogerbrugge (Elsevier, 2024)
Aims: Patients with PTEN hamartoma tumour syndrome (PHTS) have an increased risk of developing cancer due to a pathogenic germline variant in the PTEN tumour suppressor gene. Early recognition of PHTS facilitates initiation of cancer surveillance which is highly effective in preventing the development of advanced malignancies. PHTS is rare and due to its varied phenotype, even within families, oral abnormalities may be a valuable tool in the identification of these patients at an early stage before cancer development. Materials and methods: Between 1997 and 2020, phenotypic characteristics were evaluated in 81 paediatric (median age: 9 years) and 86 adult (median age: 40 years) PHTS patients by one of 2 medical experts during yearly surveillance visits at a Dutch PHTS expertise centre. Oral features evaluated included gingival hypertrophy, oral papillomas, and high palate (in adults). Results: Within adults, gingival hypertrophy was present in 94%, oral papillomas in 88%, and a high palate in 89%. All adult patients had at least one of these oral features, and 99% showed at least 2 oral features. Oral features were less common in paediatric patients, especially under 11 years of age. Gingival hypertrophy was observed in 44% and oral papillomas in 54% of paediatric patients. Conclusions: The presence of 2 or 3 oral features may indicate PHTS in adults or adolescents, especially if macrocephaly is present. Dental professionals are well-positioned to recognise these oral manifestations could be related to PHTS. They can initiate an overall clinical assessment of the patient by alerting the patient's medical practitioner of the findings and the possible need for genetic testing. This could significantly improve outcomes, including life expectancy, for patients and possibly for their relatives. Clinical relevance: Dental professionals are ideally placed to recognise oral features and initiate early assessment of PHTS which could significantly improve patient outcomes.